Interpersonal Communication Between Parents and Children in Preventing Dependence on Playing Gadgets - Rachmawati, Annisa Nur; Setyaningsih, Rila; Putri, Rahma Novita Alim (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines interpersonal communication between parents and children as an effort to prevent gadget addiction in Maguwo Village, Banguntapan, Bantul, which previously recorded cases of excessive gadget use in 2018 and 2021. The research employs a qualitative approach using Miles and Huberman's analytical framework, grounded in Joseph De Vito's theory emphasizing openness, empathy, responsiveness, positive attitudes, and supportive behavior in interpersonal communication. The study subjects include parents and children experiencing gadget addiction, with the research conducted in Maguwo Village, Banguntapan. The findings highlight the significance of openness through shared time, responsiveness reflected in authoritarian communication, and positive support. The primary challenge identified is children's mood, which influences the communication process.